EVALUATION OF HYDRAULIC FRACTURING IN THE UNCONSOLIDATED FORMATION WITH PSEUDO SKIN FACTOR METHOD - ABADI MAWAS DIRI (NIM : 22207316), DEDEK
Hydraulic Fracturing is a completion job that is commonly used for solving the formation damage problem or low permeability reservoir. The fracturing activity will be able to create the new conductive path within formation to the well bore, which in turn the hydrocarbon will easier to flow form rock formation to the well bore. In advanced practice, the hydraulic fracturing is believed as a effective completion technique to produce hydrocarbon from the unconsolidated reservoir, shallow depth, high vertical heterogeneity (high vertical permeability contrast), but the reserve is still promising. The other objective is to handle the sand problem after the job. Those two main objective is hard to accomplish with the conventional completion technique. This study is intended to evaluate the hydraulic fracturing that has been performed during 2007-2008 executed by one of Service Company, using pseudo skin factor concept. Based on this concept, the parameter of Dimensionless Conductivity is the main variable on effective hydraulic fracturing design. The detail evaluation using pseudo skin factor concept is applied in one of the well sample. The evaluation on the other wells will be performed by generating some correlations for each fracturing parameters, to see how close the correlation result with the original concept. According to correlation analysis, the pseudo skin factor is applicable to be implemented in the subject wells. The less Dimensionless Conductivity close to 1.6, the higher Fold of Increase resulted. Implementing low number of Dimensionless Conductivity combined with aggressive pad efficiency design will be able to create Tip Screen Out, which in turn will reduce the sand problem in the unconsolidated formation.